Fuzz-C automatic dustbin / Siti Nabilah Abdullah - Abdullah, Siti Nabilah (2011)
The embedded system is one kind of popular technology in many application areas. Nowadays the demand of usage these systems have increased. This project is about to develop an automatic dustbin using fuzz-C language. Fuzz-C used the similar technique in fuzzy logic but fuzz-C more compatible to be used when dealing with hardware. There are two main areas in this project which are software and hardware development. The first step required to build an embedded system project is to choose a suitable compiler to execute the instruction. Practically, from the expert experience they usually used HI-TECH compiler since it has stable technology in this area. All the build instruction have to be executed to see whether the result is success or not. However, if the execution produces success result, it is not necessarily the hardware can function well. Thus, hardware development in this project is also important. The specification components need to be identified in order to build a complete circuit. As a result, this project will get an input from the sensor and drives the motor to open the dustbin lids. It is hoped that in the future, will be improved in many ways especially in the hardware development.